Appearance and morphologic features of laryngeal tuberculosis using laryngoscopy: A retrospective cross-sectional study. Issue 51 (18th December 2020) - Zang, Jian; Tian, Ying; Jiang, Xuejun; Lin, Xu-Yong
Abstract : Abstract: Laryngeal tuberculosis (LTB) is highly contagious and can cause permanent laryngeal damage. Therefore, correctly identifying laryngoscopic LTB lesion locations, sizes, and morphologic features are essential for LTB diagnoses. This study aimed to explore the appearance and morphologic features of LTB and correlated these features with clinical symptoms. We retrospectively analysed 39 LTB patients in our hospital between January 2013 and December 2019. Medical records, including clinical presentation, lesion appearance (locations, sizes, and morphology), complementary examination results, and histopathologic features were summarized and analysed. In this patient cohort, dysphonia and sore throat were the two most common clinical symptoms. In LTB patients with extensive lesions, ulcerative lesions were most common, and the proportion of cases with concurrent pulmonary tuberculosis (86.4%, P = .033) infection was higher, as were the positive rates of sputum smears (72.7%, P = .011) and cultures (86.4%, P = .002) than patients without concurrent pulmonary TB and with more localized and exophytic lesions. The histopathologic features of LTB-related ulcerative lesions included fewer granulomas and more areas with caseous necrosis. These lesions were more likely to have acid-fast bacilli detected with a Ziehl–Neelsen stain than exophytic lesions that rarely showed detectable bacilli. A complete knowledge regarding the visual and morphologic features of LTB on laryngoscopy is needed for the early detection and diagnosis of LTB. Our study revealed the lesion sites, sizes, and morphologic features of LTB. These parameters were also correlated with patient clinical symptoms. Future studies are needed to support and expand the results of this retrospective study.